Optimization of Growth Conditions to Enhance PHA Production by Cupriavidus necator - Soňa Ronďošová; Barbora Legerská; Daniela Chmelová; Miroslav Ondrejovič; Stanislav Miertuš (Fermentation, 2022)
The accumulation of polyhydroxyalkanoates (PHAs) by microorganisms usually occurs in response to environmental stress conditions. Therefore, it is advantageous to choose two-step cultivation. The first phase is aimed at maximizing biomass production, and only in the second phase, after setting the suitable conditions, PHA production starts. The aim of this work was to optimize the composition of the minimal propagation medium used for biomass production of Cupriavidus necator DSM 545 using the response surface methodology (RSM). Based on the results from the search for optimization limits, the glucose concentration, the ammonium sulfate concentration and the phosphate buffer molarity were chosen as independent variables. The optimal values were found as follows: the glucose concentration 10.8 g/L; the ammonium sulfate concentration 0.95 g/L; and the phosphate buffer molarity 60.2 mmol/L. The predicted biomass concentration was 4.54 g/L, and the verified value was at 4.84 g/L. Although this work was primarily focused on determining the optimal composition of the propagation medium, we also evaluated the optimal composition of the production medium and found that the optimal glucose concentration was 6.7 g/L; the ammonium sulfate concentration 0.60 g/L; and the phosphate buffer molarity 20 mmol/L. The predicted PHB yield was 54.7% (w/w) of dry biomass, and the verified value was 49.1%.